Distribution of short-finned squid Illex argentinus (Cephalopoda: Ommastrephidae) inferred from the diets of Southern Ocean albatrosses using stable isotope analyses. (8th June 2015) - Seco, José; Daneri, Gustavo A.; Ceia, Filipe R.; Vieira, Rui Pedro; Hill, Simeon L.; Xavier, José Carlos
Abstract : The diets of marine predators are a potential source of information about range shifts in their prey. For example, the short-finned squid Illex argentinus, a commercially fished species on the Patagonian Shelf in the South Atlantic, has been reported in the diet of grey-headed, Thalassarche chrysostoma ; black-browed, T. melanophris ; and wandering, Diomedea exulans, albatrosses breeding at Bird Island, South Georgia (54°S 28°W) in the Southern Ocean. Tracking data suggest that these birds may feed on I. argentinus while foraging in Southern Ocean waters during their breeding season. This led to the hypothesis that I. argentinus may occur south of the Antarctic Polar Front. To test this hypothesis, we used stable isotope analyses to assess the origin of I. argentinus . We compared I. argentinus beaks from the diets of the three albatross species with beaks of cephalopod species endemic to the Patagonian Shelf and others from the Southern Ocean. Our results show that I. argentinus from the diet of albatrosses at Bird Island have δ 13 C values in the range −18.77 to −15.28‰. This is consistent with δ 13 C values for Octopus tehuelchus, a typical species from the Patagonian Shelf. In contrast, Alluroteuthis antarcticus, a Southern Ocean squid, has typically Antarctic δ 13 C in the range −25.46 to −18.61‰. This suggests that I. argentinus originated from warmer waters of the Patagonian Shelf region. It is more likely that the albatross species obtained I. argentinus by foraging in the Patagonian Shelf region than that I. argentinus naturally occurs south of the Antarctic Polar Front.